Guidelines for the implementation of blended learning in a nursing college campus in Gauteng: a mixed methods study - Maré, Magdalena Elizabeth (University of the Witwatersrand, Johannesburg, 2024)
The purpose of the study is to develop guidelines on how a nurse educator can best be prepared to implement blended learning in a Nursing Education Institution in Gauteng. The readiness of nursing students and nurse educators in a nursing education institution in Gauteng was determined to serve as a point of reference for the development of guidelines to support nurse educators to implement blended learning in the institution. Blended learning is the thoughtful integration of different instructional methods that contain face to face on online components. It enhances the educational experience for nursing students, preparing them to meet the challenges of modern health care and promoting lifelong learning. The methodology used was a mixed method study, combining a quantitative survey using the Blended Learning Readiness Engagement Questionnaire (BLREQ®) to determine readiness for blended learning amongst nursing students and nurse educators, and two focus groups with nursing education managers and nurse educators respectively. The focus groups were done to determine how best nurse educators can be supported to offer blended learning in the Nursing education institution. The Community of Inquiry framework was used to analyse the data from the focus groups and the data from Section C of the BLREQ®. According to the survey, both nursing students and nurse educators perceived themselves as ready for the implementation of blended learning, although there are gaps in their technical abilities and ability to navigate online environments. The qualitative data revealed that both nursing students and nurse educators need support and guidance for the implementation of blended learning. Nursing education managers expressed that nursing educators are still using traditional methods of teaching and that they need to be supported to use innovative teaching methods such as blended learning through regular skills development sessions. Nurse educators and students also indicated that they are not confident in participating in online platforms and discussions and that they need orientation and support navigating online platforms and the current learner management system. Although both nursing students and nurse educators see themselves as having the basic digital skills, they indicated a need for training in spreadsheet, presentation, and online communication software as well as collaborative cloud computing. The availability of technology infrastructure and lack of resources for the successful implementation of blended learning in the Nursing Education Institution were identified by nursing education managers, educators, and students. Guidelines were developed to assist the nursing education managers, nurse educators and students to address the gaps identified and to orientate new students and nurse educators to navigate the blended learning environment to assist them to adapt to new technologies and ways of learning and teaching
A Dissertation submitted for the requirements for the degree Master of Science in Nursing in the Department of Nursing Education at the University of the Witwatersrand, Johannesburg 2024
Keywords: Blended learning; Community of Inquiry in Nursing studies; Guidelines for blended learning; UCTD; SDG-3: Good health and well-being